Liparis casseabria, (Malaxideae: Orchidaceae) a new species from Chin State, Myanmar - Wang, Yu-Qian; Wu, Xun-Feng; Li, Jin-Long; Zhou, Shi-Shun; Li, Ren; Liu, Qiang; Li, Lin (Phytotaxa, 2022)
Liparis casseabria, a new species of Orchidaceae, is described and illustrated from Natma Taung National Part, Chin State, Myanmar. It is morphologically similar to L. jovispluvii, but can be easily distinguished from the latter by having conspicuous underground tuber, narrowly lanceolate petals, dramatically folded lip with entire margin and emarginated apex.